Extending the model of children’s conduct problems: A cross-sectional study of the interaction of maternal temperament and character, maternal parenting practices, and their child’s effortful control - Maor Yeshua; Claude Robert Cloninger; Ada H. Zohar; Andrea Berger (PLoS ONE, 2025)
Introduction Children’s externalizing problems in kindergarten are risk-factors that can explain psychopathology at adolescence and adulthood. Hence, it is important to study the complex and multiple-layer processes that might explain and reduce their occurrence. Among the most important moderating factors are parental caregiving practices, especially maternal sensitivity, which may depend on the parent’s temperament and character. We hypothesized that maternal effortful control (a temperament trait) and cooperativeness (a character trait) interact to facilitate maternal sensitivity and their children’s self-regulation and conduct. Method One hundred and sixty-three mothers and their children participated in a cross-sectional study. The mothers completed self-report measures of effortful control (ATQ), cooperativeness (TCI), expressive encouragement (CCNES), and their children’s effortful control (CBQ) and conduct problems (SDQ). They also performed the Etch-A-Sketch task with their children, which was coded offline for behavioral indicators of mothers’ cooperativeness. A composite factor of cooperativeness was derived from the behavioral and self-report measures. Hayes’s mediation cascade model (Model 6) was used to test our primary hypothesis. Results The model explained 22.5% of the child’s conduct problems. Within the mediation model, the mother’s cooperativeness moderated the relation between her effortful control and expressive encouragement of her child’s emotions (β=.16, t(152)=2.62,p=.010). Her expressive encouragement contributed to the child’s effortful control (β=.27, t(151)=2.55,p=.012) and fewer conduct problems (β=−.21, t(150)=−2.67,p=.008). The full mediation path was found to be significant (B=−.01, 95% Bootstrap CI [−.025, −.001]). Discussion The findings suggest that maternal temperament and character trait interact in their effects on the mothers’ behaviors, and, through them, on their children’s behaviors.